If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 69h + 2h = 84 + -3h Combine like terms: 69h + 2h = 71h 71h = 84 + -3h Solving 71h = 84 + -3h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '3h' to each side of the equation. 71h + 3h = 84 + -3h + 3h Combine like terms: 71h + 3h = 74h 74h = 84 + -3h + 3h Combine like terms: -3h + 3h = 0 74h = 84 + 0 74h = 84 Divide each side by '74'. h = 1.135135135 Simplifying h = 1.135135135
| 15+1=-4(9x-4) | | 3x-3=27x+5 | | v/6+2=-1 | | 9x-5=21x+3 | | 4(3+4x)-2=58 | | 5x^6-3x^3+1=0 | | 3(4x+7)=-47+8 | | 3(x-2)=3(x-2)+6 | | 7x^2-10xy+3y^2=0 | | 7x+13=5x+7 | | -(5x+1)=-7x+3 | | 15-x=-12 | | 9x^2-21xy-18y^2=0 | | .25w+4=-3(.25w+2)+8 | | -(6y+4)-(-5y-6)=-2 | | 8(5+4)= | | -3x+21=3x-21 | | x^4-10x^2-96=0 | | -50z-0.2=-60z+1.4 | | 8n-(3n+8)=32 | | -6y-1=5y-2 | | -[8x-(2x+7)]=1-(9x+3) | | 12+33=-5(2x-9) | | 3(7-x)-33=21x-4(3+6x) | | -8-(-n)=1 | | 8+24=-4(6x-8) | | -175=-29x-30 | | 2x^3-2x+9x^2-24x=0 | | 12x-3=24+5 | | 5x(4x+45)=360 | | -175=-29-30 | | 8n-(6n+7)=1 |